Implementation of Bureaucratic Reform in the Regional Secretariat of Ternate City: Evaluative Analysis of Organizational Change, Performance, and Public Services - Rasty Amalia; Rustam Hasim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to evaluate the implementation of bureaucratic reform in the Ternate City Regional Secretariat with a focus on three main aspects: organizational change, improving apparatus performance, and quality of public services. Bureaucratic reform is a systematic effort to realize effective, efficient, and accountable governance. A qualitative approach with a case study method is used to gain a deeper understanding, through in-depth interviews, direct observation, and analysis of policy documents. The results of the study indicate that bureaucratic reform has encouraged organizational restructuring, improved work systems, and increased human resource competency. However, its implementation still faces challenges in the form of internal resistance, budget constraints, and suboptimal supervision. On the other hand, there have been improvements in employee performance and public perception of more responsive public services. The conclusion of this study shows that although the implementation of bureaucratic reform has not been fully optimal, it has had a positive impact on the transformation of governance in the Ternate City Regional Secretariat.